Prevalence of Gastrointestinal Parasites in Pigs in Bali - Pinatih, Ayu Komang Ria Trie Dewi; Lastuti, Nunuk Dyah Retno; Kusnoto, Kusnoto; Mufasirin, Mufasirin; Yunus, Muchammad; Rahardjo, Dadik (Jurnal Medik Veteriner, 2024)
This study aimed to identify gastrointestinal parasites in pigs in Bali. A total of 117 pig feces samples were collected in Buleleng Regency (n = 67) and Jembrana (n = 50). Samples were examined microscopically using native, sedimentation, and floating methods. The results reported the prevalence of gastrointestinal parasites infecting pigs in Bali was 94.8% (111/117) infected with protozoa, namely Eimeria sp. (90.5%), Entamoeba sp. (26.4%), Isospora suis (6.8%), and Balantidium sp. (5.1%), while 99.1% (116/117) were infected with helminths, namely Trichuris suis (71.7%), Strongyloides sp. (64.9%), Ascaris suum (49.5%), Oesophagostomum sp. (6.1%), Macracanthorhyncus sp. (2.5%), and Hyostrongylus sp. (0.8%). Based on the tree regression analysis reported that the rearing system was related to the degree of gastrointestinal parasite infection in pigs in Bali.